Operando Terahertz Spectroscopy of Solid Electrolyte Interphase Evolution on Silicon Anodes. Issue 1 (19th October 2021) - Krotkov, Daniel; Schneier, Dan; Menkin, Svetlana; Horowitz, Yonatan; Peled, Emanuel; Golodnitsky, Diana; Fleischer, Sharly
Abstract: The in‐situ characterization of materials and interphases of battery electrodes is of crucial importance for the basic understanding of the complex, simultaneous processes that take place during the operation of secondary batteries. Here we present, for the first time, the use of a Terahertz (THz) time‐domain‐spectroscopy method for the operando characterization of the silicon/electrolyte interfacial phenomena and dynamics in a working lithium‐ion battery. Strong correlation between the THz, XPS, and electrochemical data was established, allowing us to monitor the formation and evolution of the solid electrolyte interphase (SEI) during the reversible lithiation of the silicon anode. Abstract : Operando characterization of solid electrolyte interphase formation : This work utilizes Terahertz time‐domain reflectometry for non‐invasive, operando monitoring of a working electrochemical cell. The developed methodology is primarily sensitive to the state of the SEI layer formed on a Silicon anode and enables on‐line monitoring of the SEI evolution throughout charge‐discharge cycling of the cell.